Acute lymphoblastic leukaemia: four-year survivals old and new. Issue 3 (March 1981) - Hardisty, R M; Till, M M; Peto, J
Abstract : Two groups of four-year survivors with acute lymphoblastic leukaemia (ALL) are compared: an 'old' series consisting of 83 patients diagnosed before 1968, and a 'new' series of 366 patients included in Medial Research Council trials (UKALL I-III) and diagnosed in 1970-4. Both series differed significantly from a group of ALL patients who survived less than four years in having lower total leucocyte and blast-cell counts at diagnosis, but the new series did not show the significant differences in organ involvement and platelet count seen in the old series. In both series, girls were more likely than boys to survive for four years and less likely to have relapsed meanwhile; in the new series, relapse rates were also lower for girls than for boys after four years, and subsequent survival was significantly better. There was no difference between the two series in survival rates of those patients who had relapsed before reaching four years. A much higher proportion of the new series, however, had reached four years without prior relapse, and these had a more favourable subsequent survival than the corresponding group of the old series. About 90% of patients achieving four years' continuous complete remission on these UKALL regimes seem likely to survive for 10 years.